Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

y = (x²+3)(2x-6)
What is the derivative?


Sagot :

Answer:

y = (x²+3)(2x-6)

  • dy/dx=d(x²+3)(2x-6)/dt=(x²+3)d(2x-6)/dt+(2x-6)d(x²+3)/dt= (x²+3)(2)+(2x-6)(2x)=2x²+6+4x²-12x=6x²-12x+6=6(x²-2x+1)